PENGARUH PEMBERIAN BEBERAPA JENIS PUPUK KOTORAN HEWAN DAN KONSENTRASI AIR KELAPA TERHADAP HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill.) - Ritawati, Sri; Firnia, Dewi; Rosyitah, Ita (Jurnal Agroekoteknologi, 2017)
This research was aimed to know the giving of some cattles manures and coconut water concentration to yield of tomato (Lycopersicum esculentum mill). This research had been conducted in the experimental farm Singamerta Institute for Agricultural Technology Banten. Starting from September to December 2013. The research used Randomized Completely Block Design, concisted of two factors. The first factors was the giving of cattles manures with three levels, they were: P0 (control), P1 (chicken manure) and (P2) cow manure. The second factor was coconut water concentration with four levels, they were: K0 (control), K1 (coconut water concentration 500 ml + water 500 ml), K2 (coconut water concentration 750 ml + water 250 ml ) and K3 (coconut water concentration 1000 ml). The result showed that the giving chicken manure gave the significant effect on number of fruits (4,53 fruit), the weight of fruits (84,63 g), diameter of fruits (28,16 mm). While the 1000 ml of coconut water concentration gave the significant effect on the weight of fruits (85,10 g) and the diameter of fruits (28,68 mm).Keywords : tomato, cattles manures, coconut water